Bioconversion of Organic Waste into Maggot (Hermetia illucens) as a Protein Source in Fish and Poultry Feeds - Kusuma Wardhani, Hilda Aqua; Ratnasari, Desi; Kurnianto, Alexander Andi (Jurnal Biologi Tropis, 2025)
Waste is an environmental problem faced by Indonesian society along with population growth. The high population growth causes an increase in waste generated by the community, both organic and inorganic waste. Organic waste management requires special attention so that innovations are needed in waste management that are not only environmentally effective, but also have economic value. One of the innovations in organic waste management is the bioconversion method. Dengan menggunakan metode telaah sistematis, penelitian ini bertujuan untuk melakukan telaah pustaka terkait potensi biokonversi limbah organik menjadi maggot sebagai sumber protein pada pakan ikan dan unggas. Pemanfaatan maggot, Hermetia illucens atau yang dikenal juga dengan sebutan Black Soldier Fly (BSF), dalam proses penguraian limbah organik, baik tumbuhan maupun hewan, telah dilaporkan dalam sejumlah penelitian sebelumnya. Pengumpulan data dilakukan dengan mengacu pada panduan Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) yang terdiri dari empat kegiatan, yaitu identifikasi artikel, penyaringan artikel, kelayakan, dan penyertaan. The results showed that Black Soldier Fly (BSF) can be utilised as a decomposer of organic waste through the bioconversion method. BSF maggot contains perfect nutrients that can be utilised as a source of protein in fish or poultry feed.